Catching the Bus: Searching for Equity in Four Massachusetts Regional Transit Systems. - Partridge, Jessie. (2017)
Abstract: Regional public transportation in Massachusetts has been getting increased attention at the state level over the past couple of years. Between efforts of the state government, regional agencies involved in transit planning and operation, and regional advocates for improved public transit, different stakeholders across the state are working to find ways to improve the current system. The intent of this thesis is to explore how Massachusetts' regional transit systems operate and communicate with riders, to begin to quantify areas where improved service may be beneficial, and to uncover ways regional transit planners, riders, and advocates can work together to identify gaps in service and implement improvements where necessary. It also presents an experimental visualization and quantification, using ArcGIS, of transit dependency for the regions within the study that identifies geographic locations that may benefit from increased service.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: Barbara Parmenter.; Keywords: Urban planning, and Transportation planning.